Parental comorbidity and medication use in the USA: a panel study of 785 000 live births. Issue 3 (18th March 2020) - Sun, Andrew J; Li, Shufeng; Zhang, Chiyuan A; Jensen, Tina K; Lindahl-Jacobsen, Rune; Eisenberg, Michael L
Abstract: STUDY QUESTION: How prevalent is paternal medication use and comorbidity, and are rates of these rising? SUMMARY ANSWER: Paternal medication use and comorbidity is common and rising, similar to trends previously described in mothers. WHAT IS KNOWN ALREADY: Maternal medication use and comorbidity has been rising for the past few decades. These trends have been linked to potential teratogenicity, maternal morbidity and mortality and poorer fetal outcomes. STUDY DESIGN, SIZE, DURATION: This is a Panel (trend) study of 785 809 live births from 2008 to 2016. PARTICIPANTS/MATERIALS, SETTING, METHODS: We used the IBM© Marketscan®™ database to gather data on demographic information and International Classification of Diseases codes and Charlson comorbidity index (CCI) during the 12 months prior to the estimated date of conception for mothers and fathers. We similarly examined claims of prescriptions in the 3 months prior to conception. We performed companion analyses of medications used for >90 days in the 12 months prior to conception and of any medication use in the 12 months prior to conception. MAIN RESULTS AND THE ROLE OF CHANCE: We confirmed that both maternal medication use and comorbidity (e.g. hypertension, diabetes, hyperlipidemia) rose over the study period, consistent with prior studies. We found a concurrent rise in both paternal medication use 3 months prior to conception (overall use, 31.5–34.9% during the study period; P < 0.0001) and comorbidity (CCI of ≥1 and 10.6–18.0% over study period; P < 0.0001). The most common conditions seen in the CCI were chronic obstructive pulmonary disease for mothers (6.6–11.6%) and hyperlipidemia for fathers (8.6–13.7%). Similar trends for individual medication classes and specific comorbidities such as hypertension, diabetes and hyperlipidemia were also seen. All primary result trends were statistically significant, making the role of chance minimal. LIMITATIONS, REASONS FOR CAUTION: As this is a descriptive study, the clinical impact is uncertain and no causal associations may be made. Though the study uses a large and curated database that includes patients from across the USA, our study population is an insured population and our findings may not be generalizable. Mean parental age was seen to slightly increase over the course of the study (<1 year) and may be associated with increased comorbidity and medication use. WIDER IMPLICATIONS OF THE FINDINGS: As parental comorbidity and certain medication use may impact fecundability, temporal declines in parental health may impact conception, pregnancy and fetal outcomes. STUDY FUNDING/COMPETING INTEREST(S): None. TRIAL REGISTRATION NUMBER: N/A